Political theology and Sars-Cov-2 pandemic: issues to Collective Health - Leão, Luís Henrique da Costa (Saúde e Sociedade, 2023)
This theoretical essay presents an overview of the field of political theology as an important part of political philosophy, demonstrates its relevance in the current Brazilian social and political scenario, and problematizes its intersections to the Collective Health field. in the first part, we explore the theological-political thoughts from key thinkers of this area like Saint Agostinho, Giorgio Agamben, Karl Marx, Enrique Dussel and Boaventura de Souza Santos. In the light of these authors, in the second part of this article, we describe the emergence of political-theologies in the Brazilian political scenario and sociocultural dynamics, manifested among evangelical groups during covid-19 pandemic. This pandemic situation shed light on many contradictions of Brazilian society and evidenced controversies between two lines of divergent evangelical political theologies: the conservative/antidemocratic and the progressive ones. The re-emergence of these political theologies has relevant effects regarding the responses of social groups and actions of power in the face of public health problems, which deserve greater attention of the Collective Health field. They influence the spheres of power and sociocultural dynamics in terms of health-disease-care, contributing with collective protection measures and/or encouraging risky, negligence, and negationists postures. We conclude by problematizing epistemological contributions to a renewed production of knowledge-action regarding the interface between political theology and Collective Health.